RANCANG BANGUN WEB MOBILE PEMESANAN TIKET DAN PENJADWALAN BUS PADA PO RAMAYANA (Information Technology and Telematics, 2014)
AbstractAlong with the progress of time and the development of mobile technologies is rapidly increasing, human be charged demand to adapted in the technology development. Sometimes humando not look at time in performing daily activities, the need something that the simple, one of which a matter of booking bus tickets.In the PO Ramayana Semarang all activities regarding ticketing is still done manually . Where applicable for transaction processing , scheduling and preparation of the departure of the bus still takes a long time and is not efficient . So often thedata is not appropriate or even data loss occurs and there are many other instances .Final project titled " Design and Implementation of Mobile Web Booking and Scheduling Bus Departures on Po Ramayana " aims to provide convenience to customers or service users to book bus tickets and view scheduled departure of the bus without having to come directly and queuing to get bus tickets . With mobile web based display can also help the process of ordering is done anytime and anywhere .Keyword : Booking, Bus Tickets, Mobile Web